PENGARUH METODE LATIHAN DRILL TERHADAP KEMAMPUAN SHOOTING PESERTA EKSTRAKURIKULER FUTSAL SMK PANCA KARSA SUNGAI PINYUH - Syech Zainudin; Andika Triansyah; Fitria Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the effect of the drill training method on the shootingability of futsal extracurricular participants at Panca Karsa Sungai Pinyuh VocationalSchool. This study uses an experimental method with the design of "One GroupPretest-Posttest Design". The population in this study were futsal extracurricularparticipants at Panca Karsa Sungai Pinyuh Vocational School, totaling 20 students.Samples were taken using a saturated sampling technique. The instrument used to testthe shooting ability is a shooting ability test at the goal based on the assessment rubricreference. Data analysis using t-test. Data analysis was carried out by normality testand homogeneity test. The results of the study can be concluded that there is an effectof target media modification on the accuracy of soccer shooting results, with tcount(8.9) > ttable (1.729), meaning that there is an effect of drill training method on futsalshooting ability with an increasing percentage of 29.88%.Keywords : Drill Training Method, Futsal Shooting Ability.